Alteration of Serum Immunoglobulin Levels in Woman with Ovarian Cancer - Ismail, Parween A.; Ali, Lana M. (Iraqi Journal of Pharmaceutical Sciences, 2021)
Ovarian cancer has a high mortality and delayed diagnosis. Several immunological alterations take place during ovarian carcinogenesis, and can be of value in the surveillance of the diseases. This research was conducted to evaluate serum immunoglobulin levels in women with ovarian cancer and to assess their role in disease process. The present study is composed of 85 women (mean age = 62.03±12.4 yrs) with clinically and pathologically confirmed ovarian cancer and 65 healthy females as a control group (mean age = 61±12.1 yrs). ELISA test was achieved for the determination of serum [IgG, IgA, IgM]. The findings of current study illustrated significant (P=0.001) increase in serum IgG, IgA, and IgM levels as compared to controls. Analyzing serum immunoglobulins levels might assist in identify patients with a weak prediction, the elevation of serum immunoglobulins can be considered as an indication for disease status.